The sustainable lifestyle level: How real salary increases affect adequate retirement provision. Issue 3 (3rd July 2022) - Roux, Elze-Mari; de Villiers, Johann
ABSTRACT: This article studies the effect of real increases in salary on required contribution rates when saving for retirement to maintain a Sustainable Lifestyle Level (SLL). We consider two strategies. The first sets conventional contribution rates, recalculating whenever an increase occurs. This requires smaller initial contribution rates, which then need to be increased later in the employee's working life. The second strategy requires that a constant contribution rate be maintained that allows for the anticipated increases. This rate requires a substantially higher contribution rate from the start. The result is particularly important for setting appropriate default contribution rates for defined contribution retirement funds.